2014
DOI: 10.1080/01635581.2015.967873
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis: Does Garlic Intake Reduce Risk of Gastric Cancer?

Abstract: In the past 2 decades, various epidemiological studies investigated whether garlic can positively modify the risk of gastric cancer. Garlic contains numerous sulfide compounds, including diallyl trisulfide, which have anticarcinogenic properties. We conducted a meta-analysis to determine if garlic intake reduces the risk of gastric cancer. An electronic search of MEDLINE, PubMed, and EMBASE to June 2014 was completed. There were 14 case control studies, 2 randomized controlled studies, and 1 cohort study that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 23 publications
(21 reference statements)
1
31
0
1
Order By: Relevance
“…Among the 31 studies, 11 studies (Chiavarini et al, ; Fleischauer et al, ; Guercio et al, ; Hu et al, ; Kodali & Eslick, ; Li et al, ; Turati et al, , ; Zhou et al, , ; Zhu et al, ) were about cancer and tumor outcomes (gastric cancer, colorectal cancer, upper aerodigestive tract cancer, prostate cancer, and colorectal adenomatous polyps), 13 studies (Emami et al, ; Khoo & Aziz, ; Kwak et al, ; Reinhart et al, ; Ried, ; Ried, Toben, et al, ; Sahebkar et al, ; Shabani et al, ; Stevinson et al, ; Sun et al, ; Wang et al, ; Warshafsky et al, ; Zeng et al, ) were about metabolic outcomes (serum total cholesterol [TC], high‐density lipoprotein [HDL], low‐density lipoprotein [LDL], triglycerides [TGs], fasting blood glucose [FBG], serum HbA1c, serum fructosamine, serum lipoprotein (a), and apolipoprotein B), seven studies (Reinhart et al, ; Ried, ; Ried et al, ; Rohner et al, ; Silagy & Neil, ; Wang et al, ; Xiong et al, ) were about cardiovascular outcomes (systolic blood pressure and diastolic blood pressure), and only one systematic review and meta‐analysis (Taghizadeh et al, ) was about serum C‐reactive protein levels. Finally, 50 unique outcomes extracted from the 16 most recent meta‐analyses were analyzed in this umbrella review, and the map of allium vegetable‐related outcomes is reported in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 31 studies, 11 studies (Chiavarini et al, ; Fleischauer et al, ; Guercio et al, ; Hu et al, ; Kodali & Eslick, ; Li et al, ; Turati et al, , ; Zhou et al, , ; Zhu et al, ) were about cancer and tumor outcomes (gastric cancer, colorectal cancer, upper aerodigestive tract cancer, prostate cancer, and colorectal adenomatous polyps), 13 studies (Emami et al, ; Khoo & Aziz, ; Kwak et al, ; Reinhart et al, ; Ried, ; Ried, Toben, et al, ; Sahebkar et al, ; Shabani et al, ; Stevinson et al, ; Sun et al, ; Wang et al, ; Warshafsky et al, ; Zeng et al, ) were about metabolic outcomes (serum total cholesterol [TC], high‐density lipoprotein [HDL], low‐density lipoprotein [LDL], triglycerides [TGs], fasting blood glucose [FBG], serum HbA1c, serum fructosamine, serum lipoprotein (a), and apolipoprotein B), seven studies (Reinhart et al, ; Ried, ; Ried et al, ; Rohner et al, ; Silagy & Neil, ; Wang et al, ; Xiong et al, ) were about cardiovascular outcomes (systolic blood pressure and diastolic blood pressure), and only one systematic review and meta‐analysis (Taghizadeh et al, ) was about serum C‐reactive protein levels. Finally, 50 unique outcomes extracted from the 16 most recent meta‐analyses were analyzed in this umbrella review, and the map of allium vegetable‐related outcomes is reported in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Then, 19,023 articles remained after removing the duplicates, and 18,992 articles were excluded after reviewing the titles and abstracts. Finally, 31 full-text articles (Chiavarini et al, 2016;Emami, Rouhani, & Azadbakht, 2017;Fleischauer, Poole, & Arab, 2000;Guercio, Turati, La Vecchia, Galeone, & Tavani, 2016;Hu et al, 2014;Khoo & Aziz, 2009;Kodali & Eslick, 2015;Kwak et al, 2014;Li, Ying, Shan, & Ji, 2018;Reinhart, Coleman, Teevan, Vachhani, & White, 2008;Reinhart, Talati, White, & Coleman, 2009;Ried, 2016;Ried, Frank, Stocks, Fakler, & Sullivan, 2008;Ried, Toben, & Fakler, 2013;Rohner, Ried, Sobenin, Bucher, & Nordmann, 2015;Sahebkar et al, 2016;Shabani et al, 2018;Silagy & Neil, 1994;Stevinson, Pittler, & Ernst, 2000;Sun, Wang, & Qin, 2018;Taghizadeh, Hamedifard, & Jafarnejad, 2018;Turati et al, 2014;Turati, Pelucchi, Guercio, La Vecchia, & Galeone, 2015;Wang, Yang, Qin, & Yang, 2015;Wang, Zhang, Lan, & Wang, 2017;Warshafsky, Kamer, & Sivak, 1993;Xiong et al, 2015;Zeng et al, 2012;Zhou, Ding, & Liu, 2013;Zhou et al, 2011;Zhu, Zou, Qi, Zhong, & Miao, 2014) were reviewed for further assessment.…”
Section: Re Sultsmentioning
confidence: 99%
“…In addition, apoptosis of MGC803 human gastric carcinoma cells was markedly increased by allicin, accompanied with an enhancement of expression levels of cleaved caspase-3, and the protein expression levels of p38 were also increased [153]. Notably, epidemiological studies also showed that garlic intake resulted in reduced risk of gastric cancer [154,155]. …”
Section: Garlicmentioning
confidence: 99%
“…Epidemiological evidence, mainly from case‐control studies, has likewise suggested a protective effect of garlic consumption against gastric cancer. Several meta‐analyses and one systematic review have been conducted to examine the association between garlic intake and gastric cancer risk since 2000 . The most up‐to‐date meta‐analysis included 12 case‐control studies with 11 175 patients and concluded high intake of garlic may prevent gastric cancer, with an acknowledge that further data from large cohorts are needed for conclusive confirmation .…”
Section: Introductionmentioning
confidence: 99%